2015
DOI: 10.1109/tap.2015.2462128
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Layer Circular Polarizer Based on Hybrid Meander Line and Loop Configuration

Abstract: VII. CONCLUSIONReflective diffractive gratings have numerous applications in optics and in electromagnetism, but their thickness can be a problem for applications at VHF frequencies or lower. We present a solution to this problem in the form of a thin diffractive panel that comprises resonant elements. A particular implementation was designed and tested for applications to prevent building perturbations to aircraft ILS. The screen measured only 1/34th of a wavelength in depth (1/15th of a wavelength with its p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 14 publications
0
42
0
Order By: Relevance
“…The measurement setup is illustrated in Figure , and is defined based on the procedure described in Refs. and .…”
Section: Polarizer Assessment and Performancementioning
confidence: 97%
“…The measurement setup is illustrated in Figure , and is defined based on the procedure described in Refs. and .…”
Section: Polarizer Assessment and Performancementioning
confidence: 97%
“…These strongly reject incident signals at frequencies above and below the spectral passband and therefore have the ability to provide self‐filtering of incident waves . As a general observation, the signal transmission is much lower outside of the operating frequency band than the single sheet topologies reported in References . Moreover unlike printed arrangements, radar cross‐section reduction can be achieved by printing a resistively loaded FSS (such as the one presented in Reference ) on the outermost surface of a dielectric spacer to create a microwave absorber out of band.…”
Section: Introductionmentioning
confidence: 98%
“…This structure exhibits a 3 dB AR BW of 17% centered at 14.4 GHz. More recently Fei et al showed that BWs exceeding 47% are obtainable from centrosymmetric dual‐loop elements and hybrid meander line and loop configurations …”
Section: Introductionmentioning
confidence: 99%
“…Polarizers can be realized by employing, for instance, metasurfaces, or meander lines, and so on. Among all the conversion ways, frequency selective surfaces (FSS), which provide different characteristics for horizontal and vertical components of incident.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a CP beam can be achieved by using a helix 2 as its axial mode offers many advantages such as good circular polarization performance over a wide frequency band. In addition to these three methods, employing polarizers [2][3][4][5][6][7][8][9] can be an efficient way to covert a linearly polarized (LP) beam into a CP beam.…”
Section: Introductionmentioning
confidence: 99%